PENGEMBANGAN MEDIA GRAFIS ELEKTRONIK UNTUK PEMBELAJARAN APRESIASI CERITA RAKYAT KELAS V SD - Fatimah, Siti; Wiryotinoyo, Mujiyono; Sudaryono, Sudaryono (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
Development research aims to produce products such as electronic media learning graphic comic appreciation folklore terms of aspects of the material, multimedia, and instructional design and the validation team repon of students as users. Development method used is a development model popularized by Borg and Gall (1983). The development steps are: (1) phase of the potential and problems, (2) stage of gathering information, (3) the product design stage, (4) design validation phase, (5) improvement phase Desai, (6) the trial products, (7) product revision stage; (8) the trial use; (9) product revision stage, and (10) stages of manufacture bulk products. The results showed that the overall development of the product has been well developed based on the results of the validation. Based on these data, it can be concluded that the media is developed based on the criteria of both validation and student responses as a user. Keyword: graphic media electronic, folklore apresiasi learning, development